Clinical researchQRS area monitoring during stress test: a novel index to separate normal to ischaemic patients? - Curione, Mario; Cammarota, Camillo; Cardarelli, Giambattista; Di Bona, Simonetta; Montesano, Teresa; Travascio, Laura; Colandrea, Marzia; Colotto, Marco; Ciancamerla, Massimo; Ronga, Giuseppe (Archives of Medical Science, 2008)
QRS amplitude is correlated with ventricular volume. During stress test ventricular volume changes differently in normal subjects and in ischaemic patients, in relation to different ventricular compliance. The aim of the study is to test whether monitoring of QRS area profile during stress test is able to discern ischaemic from non-ischaemic patients. 28 patients underwent SPECT myocardial perfusion imaging at rest and during bicycle stress test. Two groups were selected: group A (control), 15 subjects with normal distribution of tracer uptake at rest and after stress; group B (ischaemic patients), 13 patients with reduced or absent tracer uptake at rest in one or more areas. QRS total area time profile shows a clearly recognizable difference in patients with ischemia vs. controls. A linear correlation was found between QRS rest total area and cardiac mass in normal subjects but not in ischaemic patients (r=0.53 and r=–0.27 respectively); an inverse correlation was also found between QRS rest total area and rest left ventricular volume and left ventricular section area, evaluated with SPECT (r=–0.52 and r=–0.58 respectively). We can hypothesize that QRS total area is linked to haemodynamic changes. It might be useful to employ in clinical practice QRS area in addition to the standard ST criterion to increase diagnostic capability of the ECG stress test.